1988
DOI: 10.1192/bjp.152.2.164
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychiatry of Post-traumatic Stress Disorder

Abstract: The publication of DSM-III introduced the diagnosis Post-Traumatic Stress Disorder (PTSD), thus providing, for the first time, a framework for studying the consequences of extremely stressful events. Previously, traumatic neuroses had attracted a wide variety of labels - as wide as the experiences that produced them. Competing explanations in psychological and biological terms have characterised the approach to these disorders, and social and legal issues have added to the confusion. In recent years, psychosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Furthermore, Kolb [66] proposed that this generalized sensitivity to threatening situations perpetuates agonistic affect, such that limbic activity disrupts frontal executive systems; in particular, the frontal systems that inhibit the locus ceruleus and its noradrenergic innervations of diverse cortical and subcortical structures. A possible increase in cortical and subcortical noradrenergic activation further enhances the sensitization and activation of the trauma schema [66] [see also 150]. As a result,…”
Section: Neuropsychology Models Of Ptsdmentioning
confidence: 99%
“…Furthermore, Kolb [66] proposed that this generalized sensitivity to threatening situations perpetuates agonistic affect, such that limbic activity disrupts frontal executive systems; in particular, the frontal systems that inhibit the locus ceruleus and its noradrenergic innervations of diverse cortical and subcortical structures. A possible increase in cortical and subcortical noradrenergic activation further enhances the sensitization and activation of the trauma schema [66] [see also 150]. As a result,…”
Section: Neuropsychology Models Of Ptsdmentioning
confidence: 99%
“…Laterality has been studied in post-traumatic stress disorder (PTSD) mainly in the context of alexithymia (Zeitlin et al 1989 ;Henry, 1993), but also in studies suggesting interhemispheric communication deficit (Shalev et al 1988 ;Zeitlin et al 1989 ;Henry, 1993) and right hemisphere over-control (Watson et al 1988 ;Schiffer et al 1995). Watson et al (1988) described a neurophysiological model, introduced by Chemtob and Hamada, which is based on the hemispheric lateralization of cognition and affect. They emphasized the role of the right (non-dominant) hemisphere and of asymmetrical hemispheric function in PTSD, and suggest that ' less lateralized individuals are more prone to experience maladaptive levels of anxiety '.…”
Section: Introductionmentioning
confidence: 99%
“…Chemtob and Hamada (1984) hypothesized that individual characteristics associated with a lesser degree of cerebral lateralization for language in right-handed people, such as female gender, mixed lateral preference, and familial left-handedness, are associated with a greater likelihood of developing PTSD (Watson et al, 1988). Investigating this hypothesis, Spivak et al (1998) found that mixed lateral preference among righthanded Israeli male combat veterans was associated with increased susceptibility to combat-related PTSD.…”
mentioning
confidence: 96%